The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.1177/1747954121995610
|View full text |Cite
|
Sign up to set email alerts
|

How does the workload applied during the training week and the contextual factors affect the physical responses of professional soccer players in the match?

Abstract: The aim of this study was to examine whether match physical output can be predicted from the workload applied in training by professional soccer players. Training and match load records from two professional soccer teams belonging to the Spanish First and Second Division were collected through GPS technology over a season ( N = 1678 and N = 2441 records, respectively). The factors playing position, season period, quality of opposition, category and playing formation were considered into the analysis. The level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 41 publications
1
12
1
Order By: Relevance
“…Notwithstanding the above discussed relationships between training volume and relative match demands, our results revealed positive moderate relationships between prior training workload intensity and relative match demands. In fact, another study on 56 male professional soccer players from two different teams confirmed that the physical performance exhibited during a match could be predicted based on the training workload volume of the week leading up to the match [26]. Our findings are in contrast with the above-mentioned study which revealed that mTD and mHSR had strong associations with the previous wtTD and wtHSR loads -in terms of wtTD.…”
Section: Discussioncontrasting
confidence: 89%
See 3 more Smart Citations
“…Notwithstanding the above discussed relationships between training volume and relative match demands, our results revealed positive moderate relationships between prior training workload intensity and relative match demands. In fact, another study on 56 male professional soccer players from two different teams confirmed that the physical performance exhibited during a match could be predicted based on the training workload volume of the week leading up to the match [26]. Our findings are in contrast with the above-mentioned study which revealed that mTD and mHSR had strong associations with the previous wtTD and wtHSR loads -in terms of wtTD.…”
Section: Discussioncontrasting
confidence: 89%
“…Our findings are in contrast with the above-mentioned study which revealed that mTD and mHSR had strong associations with the previous wtTD and wtHSR loads -in terms of wtTD. Also, the same authors [26] suggested that may be preferable to maintain training intensity high while maintaining training volumes low. This may be reflected by lower total distances covered and higher high-intensity activity during training.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, this type of protocol is usually tested over very short periods (pre- or post-assessments within a week). Other contextual factors, such as the quality of opposition and coach encouragement, might also influence the responses of the players during a training week and the official matches in-between (Guerrero-Calderón et al, 2021 ). Therefore, these different methodological approaches between studies make comparisons with these findings difficult.…”
Section: Discussionmentioning
confidence: 99%